In-vivo antimalarial and toxicological evaluation of Chrozophora senegalensis A. Juss (euphorbiaceae) extracts - Ali A. Jigam, Usman. T Abdulrazaq, Martins N. Egbuta (Journal of Applied Pharmaceutical Science)
The antiplasmodial, analgesic, antiinflammatory and chronic dose effects of methanolic extract of Chrozophora senegalenesis A. Juss were studied in mice. Plasmodium berghei (NK 65 chloroquine sensitive strain) was inoculated into eighteen mice assigned to 3 groups of 6 mice each . Group I was treated with 75mg/kg bw C. Senegalensis, group II with 5mg/kg bw chloroquine phosphate (standard) and group III with 20ml/kg bw normal saline (Control). Anagelsia and antiinflammation were analysed by the Acetic acid induced abdominal constriction in mice and egg albumin induced paw oedema in rats respectively. Another set of 40 mice were divided into two groups of twenty each (test and control) and some serum parameters studied. The test animals were gavaged with extract while controls were given normal saline over a period of 5 weeks. C. senegalensis suppressed parasitemia in mice by 51.80%, had 37.05% anagelsia, and 60.92% anti-inflammatory activity. Body weights, packed cell volume and serum triacylglycerides significantly (p
Keywords: hrozophora senegalensis, Plasmodium berghei, analgesia, physiological, antiinflammation, serum.